Postpartum Patient Navigation and Postpartum Weight Retention - Michelle A. Kominiarek; Sydney Summerlin; Noelle G. Martinez; Lynn M. Yee (Thieme Medical Publishers, Inc., 2019)
Objective This study aimed to evaluate postpartum weight retention (PPWR) among women who participated in a postpartum patient navigation (PN) program. Study Design English-speaking pregnant or postpartum women receiving publicly-funded prenatal care at a hospital-based clinic were invited to receive PN services through 12 weeks postpartum. Women were eligible for this analysis if height and weight values were available. Weights at 4 to 12 weeks and up to 12 months postpartum were compared in PN and non-PN historical-control groups and analyzed as mean PPWR (difference from prepregnancy weight) and categorically as PPWR > 5kg. Results Among the 311 women, 152 participated in the PN program and 159 were historical controls. There were no differences in age, race and ethnicity, prepregnancy body mass index (BMI), nulliparity, and preterm birth between the groups (p > 0.05). At 4 to 12 weeks postpartum, mean PPWR (4.0 ± 6.7 vs. 2.7 ± 6.3 kg, p = 0.06) and PPWR > 5 kg (61/144 [42%] vs. 50/145 [34%], p = 0.15) did not differ between groups. Similarly, up to 12 months postpartum, mean PPWR (4.5 ± 7.1 vs. 5.0 ± 7.5 kg, p = 0.59) and PPWR > 5 kg (22/50 [44%] vs. 30/57 [53%], p = 0.55) did not differ between groups. Conclusion Although PN is a promising intervention to improve women's health care utilization and other associated health outcomes, in this particular navigation program, participation was not associated with PPWR at 4 to 12 weeks and up to 12 months postpartum.